Peningkatan Pengetahuan tentang Pemenuhan Gizi Remaja dan Edukasi Pencegahan Stunting - Ida Baroroh (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2022)
The problem of nutrition in Indonesia is still a serious problem. In essence, it stems from an economic situation that lacks limited knowledge about nutrition. Nutritional status is a measure of success in meeting the nutritional needs of children and the use of nutrients indicated by the child's weight and height. Nutritional needs in adolescence are very large because they are still growing. One of the main nutritional problems for adolescents in developing countries is malnutrition, which is reflected in stunting, underweight, stunted growth, and intrauterine growth retardation (IUGR) in pregnant adolescent girls. The purpose of this community service is to increase adolescent knowledge about the fulfillment of adolescent nutrition and stunting prevention education. The methods of health education carried out are (1) Socialization and Licensing, (2) Affirmation and Pre Test (3) Conducting health education regarding the fulfillment of adolescent nutrition and stunting prevention education. (4) Evaluation of the results of health education activities with Post Test. The results of this health education are expected to increase the knowledge and understanding of participants about the importance of fulfilling adolescent nutrition and stunting prevention education. The output of this activity is shown by increasing participants' knowledge about the importance of fulfilling adolescent nutrition and stunting prevention education which can be seen from the results of pre and post test questionnaires.